Metal polyphenol network modified carbon nanotube composite material as well as preparation method and application thereof
By using metal polyphenol networks to modify carbon nanotube composite materials in the interface evaporation seawater desalination materials, the problems of material dispersion and structural fragility are solved, and efficient and low-cost seawater desalination effect is achieved, and solar energy utilization and evaporation efficiency are improved. .
Patent Information
- Application Number
- CN202411347971.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
The processing of existing interface evaporation seawater desalination materials is difficult, the surface energy is high, resulting in uneven dispersion, fragile structure, and difficult to widely use. The process limitations of traditional materials lead to high costs and low efficiency.
The carbon nanotube composite material is modified by metal polyphenol networks, and photothermal material with good dispersion and mechanical strength is formed by coating metal polyphenol-modified carbon nanotube coating on hydrophilic foam and curing through freeze-thaw cycle.
It realizes high-efficiency, low-cost, salt-resistant and flexible processing of seawater desalination materials, improves solar energy utilization and evaporation efficiency, reduces evaporation enthalpy, and enhances light absorption capacity.
Smart Images

Figure CN119219974A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar seawater desalination, and in particular relates to a metal polyphenol network modified carbon nanotube composite material and a preparation method and application thereof. Background Art
[0002] At present, the shortage of fresh water caused by population growth and uneven distribution of water resources is a major problem concerning people's livelihood. Solar seawater evaporation is an important method to solve the problem of fresh water shortage. Among them, interfacial evaporation technology is considered to be a promising solar desalination technology. Compared with traditional reverse osmosis and distillation methods, interfacial evaporation technology directly uses solar energy as energy, avoiding the use of fossil energy and electricity. In addition, the evaporation process of interfacial evaporation technology is concentrated on the interface, without heating the water body, maximizing the use of solar energy and improving efficiency.
[0003] Carbon nanotubes are a type of carbon material with superior performance. They have a tubular structure composed of carbon hexagonal rings. Because of their light weight, good photothermal performance and chemical stability, they are often used as solar desalination materials. Although carbon nanotubes have good performance, they are difficult to process. They have a large surface energy and are easy to agglomerate and difficult to disperse evenly. In addition, interfacial evaporation composite materials are usually fragile in structure and have poor versatility. Summary of the invention
[0004] In view of the above defects or improvement needs of the prior art, the present invention aims to provide an interfacial evaporation seawater desalination material with high efficiency, low cost, salt resistance, good and flexible processing performance, certain mechanical strength and other properties, so as to improve the practicality of interfacial evaporation technology.
[0005] To achieve the above-mentioned purpose, according to one aspect of the present invention, a metal polyphenol network modified carbon nanotube composite material is provided, wherein the composite material is obtained by coating a photothermal coating on a substrate, wherein the substrate is a hydrophilic foam, and the photothermal coating comprises a photothermal agent and a carrier thereof, wherein the photothermal agent is a metal polyphenol network modified carbon nanotube, and the carrier of the photothermal agent is polyvinyl alcohol.
[0006] According to a second aspect of the present invention, a method for preparing a metal polyphenol network-modified carbon nanotube composite material is provided, the method comprising the following steps:
[0007] S100: adding aminated multi-walled carbon nanotubes to deionized water, adding metal polyphenols, adjusting the pH to weak alkalinity, and then ultrasonically treating to obtain a suspension;
[0008] S200: adding polyvinyl alcohol to the suspension, heating and dissolving at 95° C. for 1 to 2 hours, and obtaining a metal polyphenol-modified carbon nanotube coating;
[0009] S300: coating the coating on the hydrophilic foam surface and performing freeze-thaw cycles twice to obtain a metal polyphenol network-modified carbon nanotube composite material.
[0010] Furthermore, the concentration of the amino-modified multi-walled carbon nanotubes in the suspension is 1.5%.
[0011] Furthermore, the metal polyphenols are iron salts and tannic acid.
[0012] Furthermore, the iron salt is ferric chloride hexahydrate.
[0013] Furthermore, the concentration of tannic acid in the suspension is 1% to 2%, and the concentration of ferric chloride hexahydrate is 0.5% to 1%.
[0014] Furthermore, the concentration of the polyvinyl alcohol in S200 is 10%.
[0015] Furthermore, the hydrophilic foam is foamed polyurethane or polyvinyl alcohol foam or wood fiber sponge.
[0016] Furthermore, the freeze-thaw cycle in S300 includes: freezing at -18°C for 8 to 10 hours, and then thawing at room temperature.
[0017] According to a third aspect of the present invention, there is provided an application of a metal polyphenol network modified carbon nanotube composite material in seawater desalination.
[0018] Compared with the prior art, the present invention can achieve the following beneficial effects:
[0019] 1. The material matrix of the present invention adopts hydrophilic foam, and the photothermal agent is coated thereon in the form of a coating. Different types of foam can be selected according to needs and actual conditions, without being restricted by the process limitations of the main material. Compared with the interface evaporation seawater desalination material with the photothermal material itself as the main body, it has more flexible processing conditions, lower cost and wider application conditions.
[0020] 2. The present invention uses a metal polyphenol network to modify carbon nanotubes, tannic acid and amino multi-walled carbon nanotubes undergo Michael addition reaction and chelate with iron ions to form a modified layer on the surface of the carbon nanotubes, which has a good dispersing effect on the carbon nanotubes, is less toxic and more environmentally friendly than traditional surfactant dispersants. In addition, metal polyphenols will not basically change the physical properties of the solvent, will not cause the solvent to foam during processing, and are solid and will not be too sticky and difficult to flow like liquid surfactants.
[0021] 3. The present invention uses metal polyphenols in the photothermal agent, which have good affinity for the surface of amino-modified multi-walled carbon nanotubes and can form a hydrophilic layer on the surface, thereby reducing the surface energy of the carbon nanotubes and making them evenly dispersed. In addition, the hydrophilic groups of polyphenols can form intermediate water, which can effectively reduce the evaporation enthalpy and thus improve the water evaporation efficiency. Finally, the metal polyphenols can greatly enhance their light absorption capacity by reducing the HOMO-LUMO gap through the coordination of tannic acid and iron. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a physical photo of the metal polyphenol network modified carbon nanotube composite material in Example 1 of the present invention;
[0023] Figure 2 This is a transmission electron microscope photograph of the metal polyphenol-modified carbon nanotube suspension in Example 1 of the present invention;
[0024] Figure 3 Absorption spectra of MPC / EPU-3 prepared in Example 1 of the present invention and EPU prepared in Comparative Example 1;
[0025] Figure 4 It is a photothermal evaporation rate diagram of samples with different metal polyphenol contents in Example 1 of the present invention, samples in Comparative Example 1 and samples in Comparative Example 2 under a light intensity of 1 sun;
[0026] Figure 5 This is a photothermal evaporation rate diagram of samples with different metal polyphenol / carbon nanotube concentrations under 1 sun intensity according to Example 2 of the present invention.
[0027] Figure 6 Infrared thermal imaging images of MPC / EPU-3 prepared in Example 1 of the present invention and EPU prepared in Comparative Example 1 under a light intensity of 1 sun.
[0028] Figure 7 The evaporation enthalpy diagrams of the samples with different metal polyphenol contents in Example 1 of the present invention and the samples in Comparative Example 1 measured by DSC.
[0029] Figure 8 This is a photothermal evaporation rate diagram of samples using different hydrophilic foams under 1 sun intensity in Example 3 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0031] The invention provides a metal polyphenol network modified carbon nanotube composite material, wherein the metal polyphenol network modified carbon nanotube is used as a photothermal agent, polyvinyl alcohol (PVA) is used as a carrier of the photothermal agent, and hydrophilic foam is used as a matrix of the composite material. The metal polyphenol network modified carbon nanotube and PVA are uniformly mixed to obtain a photothermal coating, and then the coating is applied on the hydrophilic foam, and freeze-thaw solidification is performed to obtain the metal polyphenol network modified carbon nanotube composite material.
[0032] The preparation method of the metal polyphenol network modified carbon nanotube composite material comprises the following steps:
[0033] 1. Prepare a 1.5% aminated multi-walled carbon nanotube solution with deionized water as solvent, and add a certain amount of metal polyphenol composed of tannic acid and iron salt, preferably ferric chloride hexahydrate, monitor the pH value of the mixed solution with a pH meter, and add 2M NaOH solution to adjust the pH to 8-9. Under weak alkaline conditions, the aminated multi-walled carbon nanotubes and tannic acid undergo Michael addition reaction, and tannic acid is fixed on the surface of carbon nanotubes. At the same time, the catechol structure of tannic acid chelates iron ions to form a metal polyphenol coating on the surface of carbon nanotubes, which effectively disperses carbon nanotubes and enhances light absorption capacity. After ultrasonic treatment of the suspension for 20 minutes, a suspension with well-dispersed carbon nanotubes is obtained.
[0034] 2. PVA was added to the suspension at a concentration of 10%, and heated and dissolved in an oil bath at 95° C. for 1 to 2 hours to obtain a metal polyphenol-modified carbon nanotube coating.
[0035] 3. Apply the coating to the surface of the hydrophilic foam, freeze and thaw twice, and obtain the metal polyphenol network modified carbon nanotube composite material. Apply the coating to the surface of the hydrophilic foam cut into a certain shape, then freeze it at -18 degrees Celsius for 8-10 hours, and then thaw it at room temperature, freeze and thaw twice, and obtain the metal polyphenol network modified carbon nanotube composite material. The hydrophilic foam can be foamed polyurethane or PVA foam or wood fiber sponge.
[0036] The metal polyphenol network modified carbon nanotube composite material prepared by the method can be applied to seawater desalination.
[0037] The raw materials used in the following examples are: polyvinyl alcohol, brand PVA103; amino-modified multi-walled carbon nanotubes, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. Other raw materials and parts not specifically described in the present invention are not particularly limited to their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0038] The devices used in the present invention are not particularly limited and all devices commonly used in the art are adopted, and those skilled in the art are familiar with their operation and use methods.
[0039] Example 1
[0040] The specific steps of preparing the metal polyphenol network modified carbon nanotube composite material in this embodiment are as follows:
[0041] (1) Using deionized water as a solvent, a carbon nanotube suspension was prepared: 300 mg of amino-modified carbon nanotubes and 20 ml of water were placed on a magnetic stirrer and rapidly stirred for 5 min to obtain a carbon nanotube suspension with black particles visible to the naked eye;
[0042] (2) Add 200-400 mg of tannic acid and 100-200 mg of ferric chloride hexahydrate to the suspension obtained in (1), place the mixture on a magnetic stirrer and stir rapidly for 5 min to obtain a dark blue-black suspension;
[0043] (3) placing a pH meter in the suspension obtained in (2) to monitor the pH value, and slowly dropping a 1.5 M NaOH solution while stirring until the pH value reaches about 8.5, to obtain a dark purple-black suspension;
[0044] (4) subjecting the pH-adjusted suspension to ultrasonic treatment for 20 min to obtain a well-dispersed suspension with virtually no visible suspended particles;
[0045] (5) adding 2 g of PVA particles to the dispersed suspension, and then placing it in an oil bath at 95° C. and stirring and heating for 1 h until the PVA is completely dissolved to obtain a metal polyphenol network-modified carbon nanotube coating;
[0046] (6) Cut the EPU foam into a disc with a diameter of 25 mm and a thickness of 5 mm, and then take out 700 ul of the coating obtained in (5) and evenly apply it on one side of the disc.
[0047] (7) Place the sample obtained in (6) in a -18°C refrigerator and freeze for 8 h;
[0048] (8) Take out the sample and place it at room temperature for 20 minutes to melt;
[0049] (9) Repeat steps (7) and (8) once more to obtain a metal polyphenol network modified carbon nanotube composite material sample.
[0050] In this example, 3 groups of metal polyphenol network modified carbon nanotube composite material samples were prepared. The 3 groups of samples used tannic acid and ferric chloride hexahydrate with different concentrations, as shown in Table 1 for details.
[0051] Table 1 Concentrations of tannic acid and ferric chloride hexahydrate used in the preparation of each sample
[0052] serial number Tannic acid Ferric chloride hexahydrate Carbon Nanotubes MPC / EPU-1 1% 0.5% 1.5% MPC / EPU-2 1.5% 0.75% 1.5% MPC / EPU-3 2% 1% 1.5%
[0053] Example 2
[0054] The specific steps of preparing the metal polyphenol network modified carbon nanotube composite material in this embodiment are as follows:
[0055] (1) Using deionized water as a solvent, a carbon nanotube suspension was prepared: 300 mg of amino-modified carbon nanotubes and 20 ml of water were placed on a magnetic stirrer and rapidly stirred for 5 min to obtain a carbon nanotube suspension with black particles visible to the naked eye;
[0056] (2) adding 400 mg of tannic acid and 200 mg of ferric chloride hexahydrate to the suspension obtained in (1), placing the mixture on a magnetic stirrer and rapidly stirring for 5 min to obtain a dark blue-black suspension;
[0057] (3) placing a pH meter in the suspension obtained in (2) to monitor the pH value, and slowly dropping a 1.5 M NaOH solution while stirring until the pH value reaches about 8.5, to obtain a dark purple-black suspension;
[0058] (4) subjecting the pH-adjusted suspension to ultrasonic treatment for 20 min to obtain a well-dispersed suspension with virtually no visible suspended particles;
[0059] (5) adding 2 g of PVA particles to the dispersed suspension, and then placing it in an oil bath at 95° C. and stirring and heating for 1 h until the PVA is completely dissolved to obtain a metal polyphenol network-modified carbon nanotube coating;
[0060] (6) A 10% pure PVA solution was prepared according to the method of step (5), and then the coating and the PVA solution were evenly mixed in a mass ratio of 6.7:93.3, 33.3:66.7, 66.7:33.3, and 100:0, respectively, to obtain coatings with different photothermal agent contents.
[0061] (7) Cut the EPU into four discs with a diameter of 25 mm and a thickness of 5 mm, and then take out 700 ul of each of the four coatings obtained in (6) and evenly apply them on one side of the disc.
[0062] (8) The four samples obtained in (7) were placed in a -18°C refrigerator and frozen for 8 h;
[0063] (9) Take out the four samples and place them at room temperature for 20 min to melt;
[0064] (10) Steps (8) and (9) are repeated once more to obtain four metal polyphenol network modified carbon nanotube composite material samples.
[0065] In this example, 4 groups of metal polyphenol network modified carbon nanotube composite material samples were prepared. The 4 groups of samples used photothermal agents with different concentrations, as shown in Table 2 for details.
[0066] Table 2 Concentrations of carbon nanotubes, tannic acid and ferric chloride hexahydrate used in the preparation of each sample
[0067] serial number Tannic acid Ferric chloride hexahydrate Carbon Nanotubes 0.1% MPC / EPU-3 0.13% 0.07% 0.1% 0.5% MPC / EPU-3 0.67% 0.33% 0.5% 1.0% MPC / EPU-3 1.33% 0.67% 1.0% 1.5% MPC / EPU-3 2% 1% 1.5%
[0068] Example 3
[0069] The specific steps of preparing the metal polyphenol network modified carbon nanotube composite material in this embodiment are as follows:
[0070] (1) Using deionized water as a solvent, a carbon nanotube suspension was prepared: 300 mg of amino-modified carbon nanotubes and 20 ml of water were placed on a magnetic stirrer and rapidly stirred for 5 min to obtain a carbon nanotube suspension with black particles visible to the naked eye;
[0071] (2) adding 400 mg of tannic acid and 200 mg of ferric chloride hexahydrate to the suspension obtained in (1), placing the mixture on a magnetic stirrer and rapidly stirring for 5 min to obtain a dark blue-black suspension;
[0072] (3) placing a pH meter in the suspension obtained in (2) to monitor the pH value, and slowly dropping a 1.5 M NaOH solution while stirring until the pH value reaches about 8.5, to obtain a dark purple-black suspension;
[0073] (4) subjecting the pH-adjusted suspension to ultrasonic treatment for 20 min to obtain a well-dispersed suspension with virtually no visible suspended particles;
[0074] (5) Add 2 g of PVA particles to the dispersed suspension, and then place it in an oil bath at 95° C. and stir and heat for 1 h until the PVA is completely dissolved to obtain a metal polyphenol network-modified carbon nanotube coating;
[0075] (6) Cut the PVA foam and wood fiber sponge into discs with a diameter of 25 mm and a thickness of 5 mm respectively, and then take out 700 ul of the coating obtained in (5) and evenly apply it on one side of the two discs.
[0076] (7) Place the two samples obtained in (6) in a -18°C refrigerator and freeze for 8 h;
[0077] (8) Take out the two samples and place them at room temperature for 20 minutes to melt;
[0078] (9) Repeat steps (8) and (9) once more to obtain two metal polyphenol network modified carbon nanotube composite material samples.
[0079] In this embodiment, two groups of metal polyphenol network modified carbon nanotube composite material samples were prepared. The two groups of samples used different hydrophilic foam matrices: PVA foam and wood fiber sponge.
[0080] Comparative Example 1
[0081] EPU is directly cut into discs with a diameter of 25 mm and a thickness of 5 mm. No other processing is done and it is named EPU.
[0082] Comparative Example 2
[0083] The difference from Example (1) is that tannic acid and ferric chloride hexahydrate are not added. Named NCNT / EPU.
[0084] In order to better understand the performance of the samples prepared in the above examples, they were tested and characterized, and the results are as follows:
[0085] The samples prepared in Example 1 are as follows Figure 1 The suspension obtained in step (4) of Example 1 was observed using a desktop transmission electron microscope. Figure 2 As shown, it can be seen that the metal polyphenol coating is successfully attached to the wall of the carbon nanotubes, which enables the carbon nanotubes to be better dispersed in water.
[0086] The MPC / EPU-3 prepared in Example 1 and the EPU prepared in Comparative Example 1 were subjected to visible-near infrared absorption spectroscopy test. Figure 3 As shown, the metal polyphenol network modified carbon nanotube composite material proposed in the present invention can absorb most of the visible light and near-infrared light, with an absorbance of nearly 100%, and can completely cover the natural sunlight spectrum. This shows that the present invention has a high utilization rate of sunlight and can convert most of the received light into heat energy and then evaporate seawater.
[0087] The samples obtained in Example 1, Comparative Example 1 and Comparative Example 2 were tested for seawater desalination rate. A 3.5% NaCl solution was used to simulate seawater. The samples were placed in a square dish containing simulated seawater. The samples naturally floated on the water surface. A heat-insulating foam with a hole in the middle was placed on the square dish. Simulated sunlight with a light intensity of 1 sun was directly irradiated on the samples under the hole. The mass loss of the entire device over time was recorded, as shown in FIG. Figure 4 It can be seen that MPC / EPU-3 has the highest rate of 2.92 kg m -3 h -1 The rates of all samples in the examples are higher than those of comparative examples 1 and 2, which is due to the modification of carbon nanotubes and the activation of water by metal polyphenols.
[0088] The sample obtained in Example 2 was subjected to the above-mentioned seawater desalination rate test. Figure 5 As the photothermal agent content increases, the evaporation rate also increases. 1.5% MPC / EPU-3 has the highest rate of 3.18 kg m -3 h -1 .
[0089] Photothermal thermal imaging tests were performed on the MPC / EPU-3 in Example 1 and Comparative Example 1. The samples were irradiated under simulated sunlight with a light intensity of 1 sun, and the temperature changes over time were recorded using an infrared camera, as shown in FIG. Figure 6 It can be seen that the maximum temperature of MPC / EPU-3 can reach 53°C, which is much higher than the comparative example NCNT / EPU without adding metal polyphenols. High temperature is conducive to the evaporation of seawater.
[0090] The samples obtained in Example 1 and the samples obtained in Comparative Example 1 were subjected to DSC evaporation enthalpy test. Figure 7 Compared with pure water, the evaporation enthalpy of the samples of Example 1 and Comparative Example 1 has decreased significantly, which indicates that PVA can reduce the evaporation enthalpy of water. In addition, the evaporation enthalpy of the sample of Example 1 is lower than that of the sample of Comparative Example 1. The evaporation enthalpy of the MPC / EPU-3 sample is the lowest, reaching 2039 kJ / mol, which indicates that the addition of metal polyphenols can also significantly reduce the evaporation enthalpy, greatly improving the desalination rate of the sample.
[0091] The samples obtained in Example 3 were subjected to the above-mentioned seawater desalination rate test. Figure 8 It can be seen that PVA foam and wood fiber sponge also maintain 3.0 kg m -3 h -1 and 3.2 kg m -3 h -1 This shows that the method proposed in the present invention has strong applicability and flexible processing.
[0092] The above-mentioned embodiments only express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A metal polyphenol network modified carbon nanotube composite material, characterized in that: The composite material is obtained by coating a photothermal coating on a substrate, the substrate is a hydrophilic foam, the photothermal coating comprises a photothermal agent and a carrier thereof, the photothermal agent is a carbon nanotube modified by a metal polyphenol network, and the carrier of the photothermal agent is polyvinyl alcohol.
2. A method for preparing the metal polyphenol network modified carbon nanotube composite material according to claim 1, characterized in that: The method comprises the following steps: S100: adding aminated multi-walled carbon nanotubes to deionized water, adding metal polyphenols, adjusting the pH to weak alkalinity, and then ultrasonically treating to obtain a suspension; S200: adding polyvinyl alcohol to the suspension, heating and dissolving at 95° C. for 1 to 2 hours, and obtaining a metal polyphenol-modified carbon nanotube coating; S300: coating the coating on the hydrophilic foam surface and performing freeze-thaw cycles twice to obtain a metal polyphenol network-modified carbon nanotube composite material.
3. The method for preparing the metal polyphenol network modified carbon nanotube composite material according to claim 2, characterized in that: The concentration of the amino-modified multi-walled carbon nanotubes in the suspension is 1.5%.
4. The method for preparing the metal polyphenol network modified carbon nanotube composite material according to claim 2, characterized in that: The metal polyphenols are iron salt and tannic acid.
5. The method for preparing the metal polyphenol network modified carbon nanotube composite material according to claim 4, characterized in that: The iron salt is ferric chloride hexahydrate.
6. The method for preparing the metal polyphenol network modified carbon nanotube composite material according to claim 5, characterized in that: The concentration of tannic acid in the suspension is 1% to 2%, and the concentration of ferric chloride hexahydrate is 0.5% to 1%.
7. The method for preparing the metal polyphenol network modified carbon nanotube composite material according to claim 2, characterized in that: The concentration of the polyvinyl alcohol in S200 is 10%.
8. The method for preparing the metal polyphenol network modified carbon nanotube composite material according to claim 2, characterized in that: The hydrophilic foam is foamed polyurethane or polyvinyl alcohol foam or wood fiber sponge.
9. The method for preparing the metal polyphenol network modified carbon nanotube composite material according to claim 2, characterized in that: The freeze-thaw cycle in S300 includes: freezing at -18°C for 8 to 10 hours and then thawing at room temperature.
10. Use of the metal polyphenol network modified carbon nanotube composite material according to claim 1 in seawater desalination.